Improving the Ability to Dance Mokarawo Gorontalo Creative Dance Using Audiovisual Media in 4th Grade Students of SDN 1 Batudaa - Pasue, Miftania; Pulukadang, Wiwy Triyanty; Pulukadang, Mimy Astuty; Karlan, La Ode; Husain, Rustam I (Jurnal Kiprah Pendidikan, 2026)
This study addresses the research question: "Can audiovisual media enhance the Mokarawo creative dance skills of Class IV students at SDN 1 Batudaa, Gorontalo Regency?" The primary objective is to improve these students' dance abilities using audiovisual media. Employing Classroom Action Research (PTK) methodology, data were gathered through observation, tests, and documentation from 20 fourth-grade students at SDN 1 Batudaa, Gorontalo Regency. Results reveal steady progress. In Cycle I, Meeting 1, only 20% (4 students) met the dance competency criteria; by Meeting 2, this rose to 40% (8 students). In Cycle II, Meeting 1 achieved 70% (14 students), and Meeting 2 reached 85% (17 students). In conclusion, audiovisual media significantly boosts Mokarawo's creative dance skills among these students, demonstrating its effectiveness through iterative PTK cycles at SDN 1 Batudaa, Gorontalo Regency.